Dark wyng - D'Lacey, Chris (D'Lacey, Chris. Erth dragons, 2018)
The dragon Wearle is deeply divided because of the human boy, Ren, who has bonded with a pair of baby dragons and developed extraordinary new powers; but the war with the humans is not really over, and the humans have a mysterious new leader, Tywyll, who plans to lead his followers back into dragon territory--and unknown to both sides an ancient power is beginning to stir.